Role of Flagella in Host Cell Invasion by Burkholderia cepacia - Tomich, Mladen (American Society for Microbiology, 2002)
Burkholderia cepacia is an important opportunistic human pathogen that affects immunocompromised individuals, particularly cystic fibrosis (CF) patients. Colonization of the lungs of a CF patient by B. cepacia can lead not only to a decline in respiratory function but also to an acute systemic infection, such as bacteremia. We have previously demonstrated that a CF clinical isolate of B. cepacia, strain J2315, can invade and survive within cultured respiratory epithelial cells. In order to further characterize the mechanisms of invasion of B. cepacia, we screened a transposon-generated mutant library of strain J2315 for mutants defective in invasion of A549 respiratory epithelial cells. Here we describe isolation and characterization of a nonmotile mutant of B. cepacia with reduced invasiveness due to disruption of fliG, which encodes a component of the motor-switch complex of the flagellar basal body. We also found that a defined null mutation in fliI, a gene encoding a highly conserved ATPase required for protein translocation via the flagellar type III secretion system, also resulted in loss of motility and a significant reduction in invasion. Both mutants lacked detectable intracellular flagellin and failed to export detectable amounts of flagellin into culture supernatants, suggesting that disruption of fliG and fliI impaired flagellar biogenesis. The reduction in invasion did not appear to be due to defective adherence of the flagellar mutants to A549 cells, suggesting that functional flagella and motility are required for full invasiveness of B. cepacia. Our findings indicate that flagellum-mediated motility may facilitate penetration of host epithelial barriers by B. cepacia, contributing to establishment of infection and systemic spread of the organism.